AB0040 Il-29 induces production of il-6 and il-8 in rheumatoid arthritis synovial fibroblasts via jak/stat3 and mapk/nf-kb signaling pathways. (23rd January 2014) - Wang, F.; Xu, L.; Feng, X.; Tan, W.; Zhang, M.
Abstract : Background: IL-29 (Interferon Lambda 1)is a newly described member of the interferon family, which binds to its receptor to activate JAK-STAT, MAPK or Akt signaling pathways to induce antiviral, antiproliferative, antitumor and immune responses. The immunoregulatory role of IL-29 in immune cells is still poorly understood. We previously reported that IL-29 levels were abnormally elevated in patients with rheumatoid arthritis (RA); however, the role of IL-29 in RA inflammation remains unknown. Objectives: To investigate the effect and pathway of IL-29 on the production of proinflammatory cytokines IL-6 and IL-8 in RA synovial fibroblasts (RA-FLS). Methods: Human RA synovial fibroblast cell line, MH7A cells, were stimulated with IL-29 with or without inhibitors of MAPK/NF-κB and JAK/STAT3, the production of IL-6 and IL-8 was examined by real time PCR and enzyme-linked immunosorbent assay (ELISA). The phosphorylation of JNK, P38, ERK, IκB, NF-κB and STAT 3 was detected by western blot. Results: IL-29 enhanced the production of IL-6 and IL-8 in MH7A cells in a dose-dependent manner. IL-29-mediated induction of IL-6 and IL-8 was transduced via activation of phosphorylation of JNK, P38, ERK, IκB, NF-κB and STAT3. Conclusions: RA inflammation can be amplified by enhanced IL-29-mediated proinflammatory cytokine production on synovial fibroblasts. Our results provide the initial evidence that IL-29 may be a new target in the prevention of inflammation and joint destruction in RA. References: Wang F, Xu L, Feng X, Guo D, Tan W, Zhang M. Interleukin-29 modulates proinflammatory cytokine production in synovial inflammation of rheumatoid arthritis. Arthritis Res Ther, 2012. 14(5): R228. Acknowledgements: This project was sponsored by the grants from the National Natural Science Foundation of China (No. 30901332, 81172845, 81273294); the Key Project of the Natural Science Foundation of Jiangsu Province, China (No. BK2011851, BK2012875); the Graduate Innovation Project of Jiangsu Province, China (No. CXZZ11-0701) and the Priority Academic Program Development of Jiangsu Higher Education Institutions (PAPD). Disclosure of Interest: None Declared